Engineering human immunodeficiency virus 1 protease heterodimers as macromolecular inhibitors of viral maturation. - McPhee, F (1996)
Dimerization of human immunodeficiency virus type 1 protease (HIV-1 PR) monomers is an essential prerequisite for viral proteolytic activity and the subsequent generation of infectious virus particles. Disruption of the dimer interface inhibits this activity as does formation of heterodimers between wild-type and defective monomers. A structure-based approach was used to identify amino acid substitutions at the dimer interface of HIV-1 PR that facilitate preferential association of heterodimers and inhibit self-association of the defective monomers. Expression of the designed PR monomers inhibits activity of wild-type HIV-1 PR and viral infectivity when assayed in an ex vivo model system. These results show that it is possible to design PR monomers as macromolecular inhibitors that may provide an alternative to small molecule inhibitors for the treatment of HIV infection.